Prediction of the maximum credible ground motion in Singapore due to a great Sumatran subduction earthquake the worst case scenario. - Megawati, Kusnowidjaja
Although Singapore is located in a low seismicity region, huge but infrequent Sumatran subduction earthquakes might pose structural problems to medium and high rise buildings in the city. Based on a series of ground motion simulations of potential earthquakes that may affect Singapore, the 1833 Sumatran subduction earthquake (Mw=9.0) has been identified to be the worst case scenario earthquake. Bedrock motions in Singapore due to the hypothesized earthquake are simulated using an extended reflectivity method, taking into account uncertainties in source rupture process. Random rupture models, considering the uncertainties in rupture directivity, slip distribution, presence of asperities, rupture velocity and dislocation rise time, are made based on a range of seismologically possible models. The simulated bedrock motions have a very long duration of about 250s with a predominant period between 1.8 and 2.5 s, which coincides with the natural periods of medium and high rise buildings widely found in Singapore. The 90 percentile horizontal peak ground acceleration is estimated to be 33 gal and the 90 percentile horizontal spectral acceleration with 5 percent damping ratio is 100 gal within the predominant period range. The 90 percentile bedrock motion would generate base shear force higher than that required by the current design code, where seismic design has yet to be considered. This has not taken into account effects of local soil response that might further amplify the bedrock motion.
Keywords: 1833 Sumatran subduction earthquake; Worst case scenario earthquake; Singapore; Synthetic seismogram; Bedrock motion intensity